Discovering sanctuaries for the Endangered thick-shelled river mussel Unio crassus in Kaliningradskaya Oblast, Russia - Igor Popov; Mikhail Markovets; Evgeny Abakumov (Oryx)
The thick-shelled river mussel Unio crassus is categorized as Endangered on the IUCN Red List, and searching for surviving populations is urgent. We surveyed for this species in Kaliningradskaya Oblast, a Russian territory lying between Poland and Lithuania, where empty shells of the species had been reported from two rivers. There are at least 125 rivers and numerous small streams in the region, and as a comprehensive survey of all of these watercourses is infeasible, we used a method developed for surveys of the freshwater pearl mussels Margaritifera margaritifera and Margaritifera laevis. This involved a remote assessment of the forests and lakes in the river basins to identify sites potentially suitable for U. crassus based on criteria used for pearl mussels, followed by site surveys. We surveyed six sites and discovered U. crassus in five of those, only two of which support healthy populations. The existence of other U. crassus populations in Kaliningradskaya Oblast is unlikely. This study underscores the critical role of riparian arboreal vegetation for freshwater mussels. The conservation of U. crassus in rivers surrounded by farmlands is challenging because of siltation, eutrophication and other processes that negatively impact the riverine environment. Even the abandonment of these farmlands does not necessarily lead to improvements in mussel survival. Any plans for the restoration of U. crassus will require concurrent restoration of riparian arboreal vegetation.